1999
DOI: 10.1099/0022-1317-80-5-1241
|View full text |Cite
|
Sign up to set email alerts
|

Coreceptor usage of BOB/GPR15 and Bonzo/STRL33 by primary isolates of human immunodeficiency virus type 1.

Abstract: Primary isolates of human and simian immunodeficiency viruses (HIV andSIV

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
37
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(40 citation statements)
references
References 37 publications
3
37
0
Order By: Relevance
“…Although the in vivo expression pattern of these additional coreceptors is not well defined, preliminary reports based mainly on detection of mRNA expression levels have suggested that most of these candidate receptors are expressed on CD4 ϩ HIV-1 target cells (9,13,19,26,38,39,45,52). In general, alternative coreceptors are irregularly used by HIV-1 and appear to be less efficient than CCR5 and CXCR4 (5,15,42,45,57). Contradictory results for HIV-1 coreceptor specificities of certain HIV-1 strains have been obtained depending on the assay system used (2,15,42,44).…”
Section: Discussionmentioning
confidence: 99%
“…Although the in vivo expression pattern of these additional coreceptors is not well defined, preliminary reports based mainly on detection of mRNA expression levels have suggested that most of these candidate receptors are expressed on CD4 ϩ HIV-1 target cells (9,13,19,26,38,39,45,52). In general, alternative coreceptors are irregularly used by HIV-1 and appear to be less efficient than CCR5 and CXCR4 (5,15,42,45,57). Contradictory results for HIV-1 coreceptor specificities of certain HIV-1 strains have been obtained depending on the assay system used (2,15,42,44).…”
Section: Discussionmentioning
confidence: 99%
“…These patterns of coreceptor usage correspond to the phenotypes previously defined by the MT-2 assay; here, syncytium-inducing (SI) viruses use CXCR4, while non-syncytium-inducing (NSI) viruses use CCR5 (3). Some isolates from AIDS patients can also use other chemokine receptors as coreceptors in receptor-transfected cell lines, including CCR1, CCR2b, CCR3, BOB (GPR15), and CXCR6 (Bonzo/STRL33) (14,18,39,45,61,63; G. Alkhatib, F. Liao, E. A. Berger, J. M. Farber, and K. W. Peden, Letter, Nature 388:238, 1997). Rarely, however, are such alternative coreceptors used in primary cells (45,64).…”
mentioning
confidence: 99%
“…The major coreceptor for the macrophage-tropic, nonsyncytium-inducing (NSI) viruses, now designated R5 isolates, was found to be CCR5 (2,20,22,27,28). A plethora of other coreceptors has also been described to function for HIV-1 entry, especially for SI viruses, at least in the context of coreceptor-transfected cells in vitro (5,19,20,22,27,31,32,38,40,50,60,62,84,85,92,93,96,102,104,105,116).…”
mentioning
confidence: 99%
“…The broad tropism of SI viruses in coreceptor-transfected cell lines is well known (5,19,20,22,27,31,32,38,40,50,60,62,84,85,92,93,96,104,105,116). However, the growth of HIV-1, HIV-2, and SHIV isolates in GHOST-CD4 cells transfected with other coreceptors was only rarely comparable to the replication of the same viruses in CCR5-or CXCR4-expressing cells.…”
mentioning
confidence: 99%